Genome-wide association mapping of resistance to septoria nodorum leaf blotch in a nordic spring wheat collection - Ruud, A.K.; Dieseth, J.A.; Ficke, A.; Furuki, Eiko; Phan, Huyen T. T.; Oliver, Richard; Tan, Kar-Chun; Lillemo, M. (CROP SCIENCE SOC AMER, 2019)
Parastagonospora nodorum is the causal agent of Septoria nodorum leaf blotch (SNB) in wheat (Triticum aestivum L.). It is the most important leaf blotch pathogen in Norwegian spring wheat. Several quantitative trait loci (QTL) for SNB susceptibility have been identified. Some of these QTL are the result of underlying gene-for-gene interactions involving necrotrophic effectors (NEs) and corresponding sensitivity (Snn) genes. A collection of diverse spring wheat lines was evaluated for SNB resistance and susceptibility over seven growing seasons in the field. In addition, wheat seedlings were inoculated and infiltrated with culture filtrates (CFs) from four single spore isolates and infiltrated with semipurified NEs (SnToxA, SnTox1, and SnTox3) under greenhouse conditions. In adult plants, the most stable SNB resistance QTL were located on chromosomes 2B, 2D, 4A, 4B, 5A, 6B, 7A, and 7B. The QTL on chromosome 2D was effective most years in the field. At the seedling stage, the most significant QTL after inoculation were located on chromosomes 1A, 1B, 3A, 4B, 5B, 6B, 7A, and 7B. The QTL on chromosomes 3A and 6B were significant both after inoculation and CF infiltration, indicating the presence of novel NE–Snn interactions. The QTL on chromosomes 4B and 7A were significant in both seedlings and adult plants. Correlations between SnToxA sensitivity and disease severity in the field were significant. To our knowledge, this is the first genome-wide association mapping study (GWAS) to investigate SNB resistance at the adult plant stage under field conditions.